Effectiveness of Long-Term Treatment with Brodalumab on Anxiety or Depressive Symptoms in Japanese Patients with Psoriasis: The ProLOGUE Study - Chika Ohata; Yasumasa Kanai; Kenta Murotani; Fumikazu Yamazaki; Hidetoshi Takahashi; Yayoi Tada; Tomotaka Mabuchi; Yoko Mizutani; Takanobu Nomura; Shinichi Imafuku (Adis, Springer Healthcare, 2023)
Abstract Introduction Evidence on treatment effectiveness in patients with psoriasis having anxiety or depressive symptoms helps shared decision-making. This single-arm, open-label, prospective study-ProLOGUE-was conducted to assess the effectiveness of brodalumab on self-assessed anxiety and depressive symptoms in Japanese patients with psoriasis. Methods Patients aged ≥ 18 years with plaque psoriasis without peripheral arthritis symptoms who had responded inadequately to current therapies were enrolled at 15 Japanese facilities and received brodalumab 210 mg subcutaneously. Results A total of 73 patients were enrolled (male, 82%; median age, 54 years). The proportion of patients without anxiety symptoms changed significantly from baseline (72.6%) to weeks 12 (88.9%, p = 0.008) and 48 (87.7%, p = 0.02); the proportion of patients without depressive symptoms did not change significantly. The Generalized Anxiety Disorder-7 score (median [quartile(Q)1-Q3], 1.0 [0.0-5.0] at baseline; 0.0 [0.0-2.0] at week 12, p = 0.008; and 0.0 [0.0-1.0] at week 48, p = 0.007) and Patient Health Questionnaire-8 score (median [Q1-Q3], 2.0 [0.0-4.0] at baseline; 1.0 [0.0-4.0] at week 12, p = 0.03; and 0.0 [0.0-2.0] at week 48, p = 0.004) significantly decreased after treatment. The median Psoriasis Area and Severity Index scores after treatment were < 1, irrespective of the presence of baseline anxiety or depressive symptoms. At week 12, the health-related quality of life was more impaired in patients with versus without baseline depressive symptoms, which largely resolved at week 48. Conclusions Brodalumab treatment resulted in the reduction of the levels of self-assessed anxiety and depressive symptoms in Japanese patients with psoriasis. Unlike anxiety symptoms, depressive symptoms did not resolve completely with brodalumab treatment. Patients with psoriasis having depressive symptoms may require long-term treatment. Trial Registration UMIN Clinical Trials Registry identifier: UMIN000027783, Japan Registry of Clinical Trials identifier: jRCTs031180037.